Semiotika Rupa Topeng Malangan (Studi Kasus: Dusun Kedungmonggo, Kec. Pakisaji, Kabupaten Malang) - Astrini, Wulan; Amiuza, Chairil Budiarto; Handajani, Rinawati P. (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2013)
This study is intended to explore the visual configuration in such a form governance structure, the usefulness and meaning in conjunction with hue, and motion and visual properties of such a configuration on the Malangan mask. Theoretical results of this study may explain the relationship between visual dimensions and functions of visual arts in shaping the language of signs and meanings, which are expected to be generalized to a kind works of art and design transformation methods form the basis of a local character. This research combines qualitative approaches with a survey method. The main instrument in the form of pictures and recordings of physical configurations such visual mask. Supporting instrument in the form of interviews with actors, craftmen, and artists in Malangan mask at Kedungmonggo, Pakisaji District, Malang Regency. This study uses selected respondents porposive sampling. Data obtained from respondents compiled to obtain an overview of visual objects that represent the scope of the visual arts Malangan mask. Results of visual configuration, motion, space, and music derived from the analysis of the relationship between them, then interpreted through interviews, analyzed to obtain an overall picture configurations art, art movement, art performances (space), music (audio) of Malangan mask as cultural work local.Â